E-Identity and Security: Study of the Role of Identity Management in Sustainable Development - Akeem, Amodu; Titilope, Ejiofor (Advances in Social Sciences Research Journal, 2022)
Globally, the ability to prove one’s identity is increasingly recognized as the basis for accessing government goods and services, including security. The level of e-identity infrastructure and security in a given society determines the degree of success or failure of accomplishing the sustainable development goals (SDGs) of the United Nations. United Nations statistics indicate that a billion people in Africa and Asia lack proof of identification. Through conceptual and qualitative analysis of data gathered from both primary and secondary sources, and with particular reference to Nigeria, the paper examined the interplay between E-identity, security and sustainable development. The paper discovered the following as threats to sustainable e-identity management in Nigeria: lack of political will to enforce legislations for e-identity management; poor planning and funding of enrollment programs (which is at the heart of facilitating the UNSDGs); citizens’ complacency to enroll; and, poor enforcement of sanctions on failure to enroll. The paper concludes among others, that effective e-management of identities is a desideratum for security and sustainable development.